Correlation between domain structure dynamics and electromechanical behavior in Sn-doped BaTiO3 - Kraft, Viktoria; Cicconi, Maria Rita; Pal, Subhajit; Kuhfuß, Michel; Khansur, Neamul Hayet; Martin, Alexander; Kimura, Koji; Takabayashi, Yasuhiro; Mibu, Ko; Hayashi, Koichi; Briscoe, Joe; Webber, Kyle Grant (Journal of Materials Chemistry C, 2025)
Lead-free photoferroelectrics are promising for multimodal energy conversion systems that can harvest diverse ambient energy sources, including light and mechanical vibrations. When multiple physical phenomena are coupled within a single material, the ferroelectric, piezoelectric, and photoresponsive properties are strongly governed by the ferroelectric domain structure and domain wall mobility. To lay the groundwork for understanding such complex couplings, this study focuses on isolating and investigating the influence of the domain structure in Sn-doped BaTiO3(BaSnxTi1−xO3) on its small-signal electromechanical behavior. Rayleigh analysis was carried out to study domain wall mobility as a function of Sn content up to 11 mol%, revealing the highest irreversible contributions around 11 mol% Sn. Additionally, domain types were investigated with spatially resolved Raman spectroscopy and piezoresponse force microscopy, and correlated with electromechanical properties. These results demonstrate that Sn doping modifies the domain sizes and shapes, impacting domain wall mobility and dielectric response. Understanding domain structure dynamics in relation to electromechanical behavior is essential for optimizing coupled photoferroelectric properties.
CRIS-Team Scopus Importer:2025-12-12